2018
DOI: 10.1016/j.sjbs.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age on slaughter performance and meat quality of Binlangjang male buffalo

Abstract: Twelve representative buffalo were selected from 22 suckling calves, 41 weaned calves, 57 reserve bulls and 20 adult bulls for slaughter. The study aims to assess the effect of age on dressing percentage, meat percentage and carcass meat yield and physico-chemical properties of longissimus dorsi and biceps femoris, and to evaluate the correlation between live weight and marbling, backfat thickness, rib eye area. The results showed that the slaughter performance and meat quality of Binlangjang male buffalo show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
2
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 22 publications
1
23
2
6
Order By: Relevance
“…Bartoň et al (2003) stated that the lower carcass values are achieved by animals of dairy breeds compared to dual purpose breeds, which we also confirmed by evaluation of the Slovak Simmental breed. Lower proportion of bones in calves 4-6 months old compared to our results found Li et al (2018).…”
Section: Resultscontrasting
confidence: 80%
See 1 more Smart Citation
“…Bartoň et al (2003) stated that the lower carcass values are achieved by animals of dairy breeds compared to dual purpose breeds, which we also confirmed by evaluation of the Slovak Simmental breed. Lower proportion of bones in calves 4-6 months old compared to our results found Li et al (2018).…”
Section: Resultscontrasting
confidence: 80%
“…The results in Table 2 show that heifers had a higher protein content (P <0.01) and a lower fat content (P >0.05) of M. longissimus thoracis et lumborum compared to the values of bulls. Li et al (2018) found that the increasing of age positively affect the proportion of proteins in the category of 12-18 month old animals and also the proportion of IMF increased even after this period. On the contrary, the share of water decreased.…”
Section: Resultsmentioning
confidence: 87%
“…Gran parte de los rebaños se encuentran distribuidos en los departamentos de Córdoba, Antioquia, Santander, Caldas, Cesar, Cundinamarca, Valle, Cauca, zonas de Llanos Orientales y Amazonas. Probablemente su crecimiento se deba a que el precio de la leche de búfala es pagado un 30% por encima de la leche de vaca, básicamente por su mayo contenido de sólidos totales, y que alcanzan el peso de sacrificio antes que el ganado vacuno indicando que es un animal precoz para producir carne con alta calidad fisicoquímica y organoléptica, por lo que el búfalo puede convertirse en un recurso cárnico de alta calidad (Li et al, 2018).…”
Section: Introductionunclassified
“…Tiene alto contenido de ácido eicosapentaenoico (EPA) y El ácido docosahexaenoico (DHA) comparada con la de ternera y cerdo los cuales son importantes para el desarrollo del cerebro. (Li et al, 2018;Uriyapongson, 2013). La calidad organoléptica de la carne de búfalo después de las 36 semanas de edad es alta y presenta mejores propiedades fisicoquímicos son más altos.…”
Section: Introductionunclassified
See 1 more Smart Citation